(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Profit growth is an important indicator in assessing a company’s financial performance because it reflects the company’s ability to increase profits over time. This study aims to analyze the effect of the Current Ratio (CR) and Debt to Equity Ratio (DER) on profit growth at PT Sumber Alfaria Trijaya Tbk for the period 2015–2025. The study uses a quantitative approach with an associative research type. The data used are secondary data obtained from the company’s annual financial statements during the study period. The sample was determined using a purposive sampling technique and obtained 11 observations. Data analysis was carried out using multiple linear regression using SPSS version 22, which began with classical assumption tests including normality, multicollinearity, heteroscedasticity, and autocorrelation tests. The results of the study indicate that partially the Current Ratio does not have a significant effect on profit growth (sig. 0.408 > 0.05), likewise the Debt to Equity Ratio does not have a significant effect on profit growth (sig. 0.984 > 0.05). Simultaneously, CR and DER also had no significant effect on profit growth (sig. 0.507 > 0.05). The coefficient of determination (R²) value of 0.156 indicates that both variables were only able to explain 15.6% of the variation in profit growth. This finding indicates that PT Sumber Alfaria Trijaya Tbk’s profit growth was more influenced by factors other than liquidity and capital structure.